Global Innovation and Economic Value - Kumar, Vijay (India Studies in Business and Economics,, 2018)
This book attempts to capture innovation outcomes. The intent is on a holistic assessment of value creation by innovation - the societal value that it delivers to humanity, the economic value that it has the potential to endow to nations, and the monetary value that it provides to innovating firms. With a range of anecdotal examples and empirical analysis, the book endeavours to answer the question: Have investments in innovation paid off? Big data and analytics underpin the development of the book material. The coverage is truly global, accentuating the economic value created by innovation in the technology and pharmaceutical sectors, the two largest bastions of innovation. In addition, it includes numerous examples of successful innovation in global companies while analyzing its economic/financial impact.